2020
DOI: 10.3390/biom10111477
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Enrichment of Medaka Ovarian Germline Stem Cells by a Combination of Density Gradient Centrifugation and Differential Plating

Abstract: Fish ovarian germline stem cells (OGSCs) have great potential in various biological fields due to their ability to generate large numbers of mature eggs. Therefore, selective enrichment of OGSCs is a prerequisite for successful applications. To determine the optimal conditions for the enrichment of OGSCs from Japanese medaka (Oryzias latipes), we evaluated the effects of Percoll density gradient centrifugation (PDGC), differential plating (DP), and a combination of both methods. Based on cell morphology and ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
0
6
0
1
Order By: Relevance
“…After centrifugation, desired cells harboring a specific range of densities, which form bands between Percoll layers, are harvested for transplantation. For example, in zebrafish and medaka, as GSCs were abundant in 25–35% density Percoll fractions, cells harvested from these fractions were subjected to transplantation [ 69 , 70 ].…”
Section: Factors Affecting the Success Of Germ Cell Transplantationmentioning
confidence: 99%
See 2 more Smart Citations
“…After centrifugation, desired cells harboring a specific range of densities, which form bands between Percoll layers, are harvested for transplantation. For example, in zebrafish and medaka, as GSCs were abundant in 25–35% density Percoll fractions, cells harvested from these fractions were subjected to transplantation [ 69 , 70 ].…”
Section: Factors Affecting the Success Of Germ Cell Transplantationmentioning
confidence: 99%
“…Enrichment methods can be used solely or combinedly. By combining them, the limitation of each method can be mitigated, which would lead to higher purities than those of enrichment with a single method [ 70 ]. The improved purity of GSCs after enrichment resulted in an increase of colonization efficiencies (up to a 17.5-fold increase) compared to those of unsorted cells [ 19 , 20 , 62 , 70 , 73 , 86 ].…”
Section: Factors Affecting the Success Of Germ Cell Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…Since surrogate reproduction in fish is a long term and laborious effort, whole technology needs to be optimized to maximize its success. Optimal conditions for GSCs isolation (Shikina et al, 2013), purification (Ryu and Gong, 2020), and in vitro expansion (Iwasaki-Takahashi et al, 2020; Xie et al, 2019) were identified. Several studies already paid attention to the investigation of variables related to used recipients.…”
Section: Introductionmentioning
confidence: 99%
“…Em contraste a estes resultados, Ryu & Gong, (2020) observaram que os genes nanos2 e vasa apresentaram altos níveis de expressão gênica nas oogôniastronco submetidas ao plaqueamento diferencial. Este fato sugere que as condições de purificação, tal como meio, ação enzimática e período de purificação podem ter afetado a qualidade da célula.…”
Section: Oogôniasunclassified